A200 THE USE OF CAPSULE ENDOSCOPY FOR DIAGNOSIS OF IRON DEFICIENCY ANEMIA- A RETROSPECTIVE ANALYSIS. (1st March 2018) - Stone, J; Grover, K; Bernstein, C N
Abstract: Background: Many patients who present with undiagnosed iron deficiency anemia (IDA) are presumed to have occult gastrointestinal (GI) bleeding as the cause. When investigations include a negative upper endoscopy and colonoscopy, a negative celiac antibody screen and there is no obvious GI source of blood loss, occult GI bleeding from a small bowel source is considered and capsule endoscopy (CE) is pursued. Recent Canadian Association of Gastroenterology guidelines on the use of CE suggested that CE is indicated in only selected cases of iron deficiency anemia; however, evidence on the yield of CE in IDA and how to optimally select cases is limited. Aims: We aimed to examine the yield of CE in diagnosing the cause of IDA and to define clinical parameters that predict higher diagnostic yields Methods: 1351 individuals underwent CE in Manitoba between the years of 2005–2016. All studies were reported by one reading physician and all requisitions included demographics and requested information on medication use, prior imaging studies, and hemoglobin and ferritin levels. 620 (46%) CE was indicated for occult GI bleeding or IDA. Positive findings on CE were separated into 'definite' and 'possible'. Descriptive statistics are reported and multinomial regression analysis was used to determine the variables correlated with definite CE findings. Results: Of the 620 included subjects, mean age was 62.9 years, and mean hemoglobin was 89 g/L and mean ferritin was 32 uMol/L. 210 (33.9%) had positive findings (definite; 23%, possible;10.8%). 107 (17.2%) of all patients were taking ASA, 31 (5%) were on an antiplatelet agent, and 33 (5.3%) on an anticoagulant. Vascular ectasias were the majority of definite findings (47.5%). Predictors of definite findings were age (relative risk (RR) 1.04; 95% CI 1.02–1.06) and male sex (RR 1.88; 95%CI 1.25–2.83). None of serum Hg or ferritin, rural vs urban residence, number of prior upper or lower endoscopies, prior small bowel enteroscopy, use of ASA, antiplatelet, anticoagulant or PPI medications predicted a positive CE. Conclusions: To our knowledge, this is the largest study examining the use of CE in iron deficiency anemia and occult GI bleeding. The diagnostic yield of 33.9% and more importantly 23% for definite lesions is within the range of previously reported yields. Within this cohort, age and male sex are predictors of definite findings on CE. Antiplatelet agents and anticoagulants did not predict positive findings in our study. Further research is needed to determine which findings lead to interventions that positively impact on patient outcomes Funding Agencies: None